Electrodeposition of Al–Mg coating in the electrolyte system of C4H8O–C6H6–LiAlH4–AlCl3–MgX2(X=Cl, Br) - Lingling Shen; Binbin Cui; Song Li; Yizhu Lei; Zhongning Shi (Journal of Materials Research and Technology, 2023)
The electrochemical behavior of electrodeposited Al–Mg alloy coating was studied via cyclic voltammetry (CV), chronoamperometry and chronopotentiometric techniques in C4H8O–C6H6–LiAlH4–AlCl3 –MgX2 (X = Cl, Br) electrolyte, and the electrodeposites were characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). The result showed that co–deposition of Al and Mg started at −0.45 V (vs Al) attributing to the electrochemical reduction from electrochemically Mg(AlH4)2 in C4H8O–C6H6–LiAlH4 –AlCl3–MgCl2. However, co–deposition of Al and Mg started at −0.48 and −0.82 V in C4H8O–C6H6–LiAlH4–AlCl3–MgBr2, contributing from two different types of electrochemically active products, including of Mg(AlH4)2 and MgAl2Cl8. Moreover, it was suggested the electrochemical behavior of the electrochemically active materials was related not only to the applied potential, but also to the concentration of MgBr2 in the electrolyte. The CV curves showed that the electrochemical process of electrodeposited Al–Mg was not completely reversible. Moreover, it was suggested that the electrodeposition process was controlled by diffusion, and the nucleation process is identified as instantaneous nucleation. The maximum magnesium content of 13.3% can be acquired when the current density of 17.8 mA/cm2 was applied. The optimum process conditions of current density (15–21 mA/cm2) and electrodeposition time (1–1.5 h) were suggested for electrodeposition of Al–Mg alloy.